2023
DOI: 10.21203/rs.3.rs-3155391/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of stone density on the total laser time and other surgical outcomes in flexible ureteroscopy

Abstract: Several preoperative factors are assessed for the evaluation of operative time and fragmentation efficacy during retrograde intrarenal surgery. Due to limited energy capabilities, stone density is regarded as an important factor contributing to procedural time. This study aimed to evaluate the effect of stone density on the total laser time (TLT) in lithotripsy. A total of 52 patients who underwent flexible ureteroscopy (fURS) using the Cyber Ho 60 holmium laser system (Quanta System) from October 2017 to Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…Pain abdomen was the presenting complaint in a study done in India by Jagannath et al 9 In contrast to these, Jeevaraman et al 15 found hematuria as the most common clinical presentation of ureteric calculi. In our study, left ureteric calculus (49.2%) was more common which was similar to study done by Rashid et al 16 and Ali et al 17 Right ureteric calculi undergoing laser lithotripsy was slightly more common (60.7%, 50.3% and 51.4%) in studies done by Jagannath et al, 9 Abedi et al 4 and Koju et al 3 respectively. Bilateral calculi were only 7.6% in our study and this finding was similar to other studies.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Pain abdomen was the presenting complaint in a study done in India by Jagannath et al 9 In contrast to these, Jeevaraman et al 15 found hematuria as the most common clinical presentation of ureteric calculi. In our study, left ureteric calculus (49.2%) was more common which was similar to study done by Rashid et al 16 and Ali et al 17 Right ureteric calculi undergoing laser lithotripsy was slightly more common (60.7%, 50.3% and 51.4%) in studies done by Jagannath et al, 9 Abedi et al 4 and Koju et al 3 respectively. Bilateral calculi were only 7.6% in our study and this finding was similar to other studies.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to this, a study done in India showed that only 28.0% patients had calculus with density ≥1000 HU. 20 The mean density of the calculus was 1043 ± 335.2 HU in a study done by Rashid et al 16 which is lesser than our study.…”
Section: Subedi Et Alcontrasting
confidence: 75%
See 3 more Smart Citations